Safety and reliability assessment of gas pipelines under building occupation - Xingyu PENG; Guifang CHEN; Lei CHEN; Zhe ZHANG; Shiman SU (You-qi chuyun, 2022)
Building occupation is common for pipelines in urban area, which likely leads to the subsidence of foundations and deformation of pipelines and induces accidents such as oil and gas leakage, even explosions. In this study, a pipeline reliability model based on stress-strength interference was established. Meanwhile, the distribution of three random parameters under building occupation, including the additional stress under building occupation, the maximum reduced stress of dangerous pipeline sections and the pipe yield strength, were analyzed based on the theory of structural reliability. In order to achieve equivalent normalization, the variables in abnormal distribution were processed according to the classic JC algorithm, and the iterative initial value of the unknown was set based on the structural linearity performance functions to improve the convergence speed and precision of the algorithm. In addition, a reliability model of gas pipeline under the occupation of framed and brick-concrete buildings based on M-JC algorithm was established, and the reliability of the occupied pipeline was analyzed by implementing the M-JC algorithm in combination with Matlab programming. As shown by the results, the reliability of pipeline sections under the occupation of the framed and brick-concrete buildings is 0.985 2 and 0.999 8, respectively, indicating that the surface overburden load has little effect on the undamaged pipeline. In addition, the error between the results of M-JC algorithm and JC algorithm is very small, with a relative error less than 1%. Generally, the research results are applicable to the analysis on reliability of pipeline under building occupation and have reference value to the safe operation of pipelines and the urban construction planning.